2021
DOI: 10.21203/rs.3.rs-1114693/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission-selective muscle pathology induced by active propagation of mutant huntingtin across the human neuromuscular synapse

Abstract: A potential explanation for the spatiotemporal accumulation of pathological lesions in the brain of patients with neurodegenerative protein misfolding diseases (PMDs) is cell-to-cell transmission of aggregation-prone, misfolded proteins. Little is known about central to peripheral transmission and its contribution to pathology. We show that transmission of Huntington’s disease- (HD-) associated mutant HTT exon 1 (mHTTEx1) occurs across the neuromuscular junctions in human iPSC cultures and in vivo in wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The fact that mHTT is present during neuronal development raises the interest to assess whether early developmental processes, important for appropriate assembly of neuronal networks, are altered in HD patients. We used an hiPSC line bearing a doxycycline-inducible pro-neuronal transcription factor, NGN2 ( iNGN2 ), and generated a double transgenic line by introducing a HTTEx1Q72 fused to mCherry ( iNgn2; HTTEx1Q72-mCherry , hereafter HTTEx1Q72-mCherry) ( Nehme et al, 2018 ; Dinamarca et al, 2021 ). We analyzed three clones for their expression of HTTEx1Q72-mCherry and decided to use, in this study, clone#72, which showed an intermediate level of protein expression and has been shown to have a moderate aggregate formation over time ( Supplementary Figure S1 ) ( Dinamarca et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that mHTT is present during neuronal development raises the interest to assess whether early developmental processes, important for appropriate assembly of neuronal networks, are altered in HD patients. We used an hiPSC line bearing a doxycycline-inducible pro-neuronal transcription factor, NGN2 ( iNGN2 ), and generated a double transgenic line by introducing a HTTEx1Q72 fused to mCherry ( iNgn2; HTTEx1Q72-mCherry , hereafter HTTEx1Q72-mCherry) ( Nehme et al, 2018 ; Dinamarca et al, 2021 ). We analyzed three clones for their expression of HTTEx1Q72-mCherry and decided to use, in this study, clone#72, which showed an intermediate level of protein expression and has been shown to have a moderate aggregate formation over time ( Supplementary Figure S1 ) ( Dinamarca et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used an hiPSC line bearing a doxycycline-inducible pro-neuronal transcription factor, NGN2 ( iNGN2 ), and generated a double transgenic line by introducing a HTTEx1Q72 fused to mCherry ( iNgn2; HTTEx1Q72-mCherry , hereafter HTTEx1Q72-mCherry) ( Nehme et al, 2018 ; Dinamarca et al, 2021 ). We analyzed three clones for their expression of HTTEx1Q72-mCherry and decided to use, in this study, clone#72, which showed an intermediate level of protein expression and has been shown to have a moderate aggregate formation over time ( Supplementary Figure S1 ) ( Dinamarca et al, 2021 ). As a control line, we used iNGN2 hiPSCs expressing mCherry (Ctr-mCherry).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation